Phosphatidylinositol 3-kinase-dependent activation of trypsinogen modulates the severity of acute pancreatitis - Singh, Vijay P. (American Society for Clinical Investigation, 2001)
Intra-acinar cell activation of digestive enzyme zymogens including trypsinogen is generally believed to be an early and critical event in acute pancreatitis. We have found that the phosphatidylinositol 3-kinase inhibitor wortmannin can reduce the intrapancreatic activation of trypsinogen that occurs during two dissimilar experimental models of rodent acute pancreatitis, secretagogue- and duct injection-induced pancreatitis. The severity of both models was also reduced by wortmannin administration. In contrast, the NF-κB activation that occurs during the early stages of secretagogue-induced pancreatitis is not altered by administration of wortmannin. Ex vivo, caerulein-induced trypsinogen activation is inhibited by wortmannin and LY294002. However, the cytoskeletal changes induced by caerulein were not affected by wortmannin. Concentrations of caerulein that induced ex vivo trypsinogen activation do not significantly increase phosphatidylinositol-3,4-bisphosphate or phosphatidylinositol 3,4,5-trisphosphate levels or induce phosphorylation of Akt/PKB, suggesting that class I phosphatidylinositol 3-kinases are not involved. The concentration of wortmannin that inhibits trypsinogen activation causes a 75% decrease in phosphatidylinositol 3-phosphate, which is implicated in vesicle trafficking and fusion. We conclude that a wortmannin-inhibitable phosphatidylinositol 3-kinase is necessary for intrapancreatic activation of trypsinogen and regulating the severity of acute pancreatitis. Our observations suggest that phosphatidylinositol 3-kinase inhibition might be of benefit in preventing acute pancreatitis.